2017
DOI: 10.3221/igf-esis.42.20
|View full text |Cite
|
Sign up to set email alerts
|

The fatigue behavior of V-notches in presence of residual stresses: recent developments and future outcomes

Abstract: ABSTRACT. Residual stresses, arising from welding processes or nonhomogeneous plastic deformations, broadly influence the high cycle fatigue behavior of mechanical components. The presence of V-notches leads to singular residual stresses ahead of the notch tip and the asymptotic stress field can be described by the notch stress intensity factor (NSIF). However, plastic effects induce redistribution of residual stresses during cyclic loading and this variation is accounted in several numerical models developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, the volume-based approach proposed by Lazzarin and Zambardi represents a great development of all the previous strain energy density-based approaches. This method has been revealed to successfully predict both the tensile and fatigue strength of different notched materials subjected to both uniaxial and mixed-mode loading [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Piccotin et al, for example, assessed with good agreements the tensile strength under mode I, II, and mixed mode I + II of polyurethane foams characterized by different densities and weakened by several notch geometries [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the volume-based approach proposed by Lazzarin and Zambardi represents a great development of all the previous strain energy density-based approaches. This method has been revealed to successfully predict both the tensile and fatigue strength of different notched materials subjected to both uniaxial and mixed-mode loading [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Piccotin et al, for example, assessed with good agreements the tensile strength under mode I, II, and mixed mode I + II of polyurethane foams characterized by different densities and weakened by several notch geometries [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Welds represent local regions of higher stresses (i.e., stress concentrators) and fatigue failure is widely known to be sensitive to local peak stresses. Thus, over the years, several methods have been developed to assess the fatigue behavior of welds, and among these the Notch Stress Intensity Factor (NSIF) approach is worth mentioning [6][7][8]. In fact, since experimental observations have revealed that the most used welding procedures, such as arc and laser welding, are characterized by a very small weld toe radius, it is acceptable to model it as a sharp notch and the fatigue behavior can thus be correlated to the NSIFs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these significant advances in understanding the impact of processing conditions on the mechanical behaviour of parts, the effect of geometric discontinuities such as notches is so far underexplored. Yet, this is highly relevant in the field of complex geometric design as such attempts naturally introduce such discontinuities reported to strongly affect both tensile and fatigue properties of the components [16][17][18][19][20][21][22][23][24][25][26]. In fatigue, the effect of notches is unambiguous, determining a reduction in the fatigue strength for several materials [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%